NIAT MAHASISWA AKUNTANSI BERKARIR SEBAGAI AKUNTAN DI LUAR NEGERI: PENGUJIAN THEORY OF PLANNED BEHAVIOR - Madani Hatta; Agustian Riduan O.H (UNIB Press, 2017)
This study aimed to determine the factors that affect intention of accounting students career as an accountant abroad. By using TPB (Theory of Planned Behavior) model, intention of accounting students career as an accountant abroad is influenced by three factors: attitude toward behavior, subjective norm, and perceived behavioral control. Respondents in this study were diploma and undergraduate students in last semester with a number of 90 students of Department of Accounting, Faculty of Economics and Business, University in Bengkulu city. The method of collecting data in this study using a survey by distributing questionnaires to the respondents either directly or entrusted to the chairman of the accounting department at the university. The data was analyzed by using SmartPLS 3.0. The results show that attitude toward behavior and subjective norm have significant positive effect on intention of accounting students career as an accountant abroad, but perceived behavioral control have no effect on intention of accounting students career as an accountant abroad.Keywords: Theory of planned behavior (TPB), attitude towards behavior, subjective norm, perceived behavioral control.